Republic of the Marshall Islands : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
The strategy that has the best chance of allowing the Republic of Marshall Islands (RMI) to achieve fiscal sustainability after FY2023 involves substantial fiscal consolidation. The alternative (policy action) scenario involves a substantial fiscal adjustment starting in FY2009. Projections show that this strategy can succeed in achieving budgetary self-sufficiency. Fiscal consolidation will be difficult, and will have to be accompanied by structural reforms to improve real growth. Substantial fiscal consolidation in the short term is necessary to achieve budgetary self-sufficiency after 2023.